METHODS OF TEACHING RUSSIAN LANGUAGE AT UNIVERSITY (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
The article discusses the starting point in the work of a teacher, which is the mandatory minimum content of education in the Russian language. Based on these intensive work standards, the teacher distributes the curriculum in accordance with integrated teaching methods, defining the basic curriculum